TRAINING AND ASSISTANCE IN WRITING RESEARCH ARTICLES TO BE PUBLISHED IN REPUTABLE JOURNALS IN MGMP ENGLISH RAYON V JAMBI CITY - Pratama, Aryawira; Fitria, Wahyuni; Puputri, Puputri; Rozal, Edi; Dika, Dedi Sastra; Mahmudah, Khotimah; Sumardi, Mayang Sastra; Putri, Rahmadani; Nirwana, Iin; Nurhasanah, Amalia (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2024)
This service is a form of the English Education Study Program in carrying out the tridharma tasks of higher education. The aim of this service is to provide assistance and training to English teachers who are members of the MGMP Rayon 5 community in Jambi City. This activity consists of several meetings specifically with the aim of providing teachers with the opportunity to receive guidance on writing research articles for publication in journals. As a result of this activity, the teachers felt very helpful in writing research articles and they had several articles ready to be submitted to journals. In the future, the study program wants to carry out activities with an international reputation journal orientation.